2020
DOI: 10.1089/jmf.2019.4675
|View full text |Cite
|
Sign up to set email alerts
|

Perilla Oil Alleviates High-Fat Diet-Induced Inflammation in the Colon of Mice by Suppressing Nuclear Factor-Kappa B Activation

Abstract: This study aimed to evaluate the effect of perilla oil (PO) on high-fat diet (HD)-induced colonic inflammation. Male C57BL/6J mice (5 weeks old) were divided into four groups: normal diet, HD, HD supplemented with fish oil (FO), and HD supplemented with PO, and were fed experimental diets for 16 weeks. PO significantly ameliorated (P < .05) the HD-induced colon inflammation as indicated by the increased colon length and low macroscopic score. PO increased the number of Bifidobacteria and reduced the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The findings in our study are in accordance with the report that in mice, PSO rich in alpha-linolenic acid also inhibits COX-2 and iNOS expression by inhibiting the protein expression of NF-κB (p65) [72]. Moreover, it was found that PSO reduces the expression of IL-1β, IL-6, TNF-α, and COX-2 mRNA by inhibiting p65 phosphorylation in colonic inflammation induced by a high-fat diet in mice [73]. Notably, RA alone was shown to inhibit inflammation in H22 tumor-bearing mice by reducing the IL-1β, IL-6, and TNF-α levels and p65 and p-p65 expression [74].…”
Section: Discussionsupporting
confidence: 92%
“…The findings in our study are in accordance with the report that in mice, PSO rich in alpha-linolenic acid also inhibits COX-2 and iNOS expression by inhibiting the protein expression of NF-κB (p65) [72]. Moreover, it was found that PSO reduces the expression of IL-1β, IL-6, TNF-α, and COX-2 mRNA by inhibiting p65 phosphorylation in colonic inflammation induced by a high-fat diet in mice [73]. Notably, RA alone was shown to inhibit inflammation in H22 tumor-bearing mice by reducing the IL-1β, IL-6, and TNF-α levels and p65 and p-p65 expression [74].…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, we observed that PO exerts protective effects against HFD-induced colon inflammation. The effects were similar to those of FO, which was used as a positive control [18]. In the present study, we evaluated the comparative effect of endogenously produced omega-3 fatty acids in fat-1 transgenic mice and diet-supplemented omega-3 fatty acids in wild-type (WT) mice against HFD-induced colon inflammation.…”
Section: Introductionmentioning
confidence: 95%
“…It has been documented that SO fruit is a rich source of proteins, pectin, vitamins, phenolics, flavonoids, triterpenoids, and minerals, which confers its excellent medicinal, edible, and ornamental value (10,11). Especially in the field of folk medicine, SO has shown antipyretic, diuretic, dredge meridians, analgesic, and lactogenic effects, and could be used in the treatment of many diseases, such as rheumatism, beriberi, axillary carbuncle, cystitis, traumatic injury, trigeminal neuralgia, and sciatica (12,13). Although there are various positive effects on health, SO is still underutilized, only a tiny amount has been consumed as a fruit.…”
Section: Introductionmentioning
confidence: 99%